Effect of Fluoride Varnish Containing CPP-ACP on Preventing Enamel Erosion. (9th January 2017) - Bayrak, Sule; Tuloglu, Nuray; Bicer, Huseyin; Sen Tunc, Emine
Abstract : This study aimed to investigate the effect of a fluoride varnish with added casein phosphopeptide-amorphous calcium phosphate treatment on the prevention of enamel erosion, and it compared the results with those of other fluoride varnishes. Fifty enamel specimens obtained from bovine incisors were randomly divided into five groups (n = 10 ) based on the type of surface pretreatment used: intact enamel (Group 1); intact enamel+erosive cycles (Group 2); intact enamel+MI varnish+erosive cycles (Group 3); intact enamel+Clinpro White varnish+erosive cycles (Group 4); and intact enamel+Duraphat varnish+erosive cycles (Group 5). The specimens were subjected to erosive cycles for five days. The surface roughness was evaluated using atomic force microscopy. The results were statistically analyzed using one-way ANOVA and Tukey's tests. Group 1 had the smoothest surfaces. After the erosive cycles, the greatest surface roughness values were observed in Group 2, followed by Groups 5, 4, and 3, respectively. Statistically significant differences were observed among all groups (p < 0.05 ). The application of fluoride varnishes had some positive effects on preventing enamel erosion; however, the most effective agent was fluoride varnish with added casein phosphopeptide-amorphous calcium phosphate.